ESL learners’ perceptions towards the learning of literature in English - Chacko, John (2007)
The study attempts to find out the perceptions of learners in the Malaysian context towards the learning of literature in English through the use of the instructional and language-based approaches. There is a necessity to increase our understanding and awareness of the relationship between learner and teacher related factors like instructional and language-based approaches. In the Malaysian context, the learning of literature in English has an important role especially in a multiracial class that has linguistic, cultural and social differences. The respondents involved in this study were 100 Form Four learners of literature in English in an urban secondary school. To elicit their responses, questionnaires were distributed and interviews were conducted. These questionnaires were designed to obtain information regarding their demographic and educational background and more importantly their perceptions towards the learning of literature in English in relation to the instructional and language-based determinants. Descriptive statistics were used to analyse Section A and Section B that contained the demographic variables of the samples. Items in Section C of the questionnaire were measured based on a four-point Likert-type. Inferential statistics (t-test) were used to determine the group differences regarding the perceptions of the respondents across gender for the determinants. On the whole, the findings of the survey show that the respondents agreed to most of the instructional and the language-based determinants as being suitable for the learning of literature in English. The analysis of the perceptions of the respondents showed that pedagogically the instructional approach was considered a better approach in the learning of literature in English. The analysis of the perceptions of the respondents towards the instructional determinants across gender showed a significant difference for two determinants. The female respondents perceived the sociopolitical and mythological determinants to be important in the learning of literature in English than their male counterparts. The analysis across gender for the language-based determinants showed that there were four significantly different determinants. The female respondents perceived the role-play, storytelling and skits, student presentation, summary and guided-writing determinants to be important in the learning of literature in English than their male counterparts while the male respondents perceived debates and forums to be a suitable determinant for learning literature than the female respondents. Implications and suggestions for further research to enhance the learning of literature in English are considered The instructional and language-based approaches encourage self-directed learning, where the learners take on responsibility for their learning of literature. These approaches reduce the learners’ dependence on their teachers and encourage greater independence on the learners’ part. Learners will be more aware of the process involved in learning, thus enabling them to make conscious efforts in learning literature. At the same time, learners are motivated, their self-esteem high and are constantly reinforced. They become engaged in a variety of activities. The focus of this kind of experience should be in helping learners to learn how to equip themselves with tools to understand and comprehend the learning of literature. These approaches will provide valuable ideas, insights and activities to learn the literature component as a whole.